Dosimetric and efficiency comparison of high-dose radiotherapy for esophageal cancer: volumetric modulated arc therapy versus fixed-field intensity-modulated radiotherapy. Issue 6 (1st August 2014) - Lin, C.-Y.; Huang, W.-Y.; Jen, Y.-M.; Chen, C.-M.; Su, Y.-F.; Chao, H.-L.; Lin, C.-S.
Summary: The aim of this study was to compare high-dose volumetric modulated arc therapy (VMAT ) and fixed-field intensity-modulated radiotherapy (ff-IMRT ) plans for the treatment of patients with middle-thoracic esophageal cancer. Eight patients with cT2-3N0M0 middle-thoracic esophageal cancer were enrolled. The treatment planning system was the version 9 of the P innacle 3 with S martA rc (P hilips H ealthcare, F itchburg, WI, USA ). VMAT and ff-IMRT treatment plans were generated for each case, and both techniques were used to deliver 50 G y to the planning target volume (PTV 50 ) and then provided a 16-G y boost (PTV 66 ). The VMAT plans provided superior PTV 66 coverage compared with the ff-IMRT plans ( P = 0.034), whereas the ff-IMRT plans provided more appropriate dose homogeneity to the PTV 50 ( P = 0.017). In the lung, the V 5 and V 10 were lower for the ff-IMRT plans than for the VMAT plans, whereas the V 20 was lower for the VMAT plans. The delivery time was significantly shorter for the VMAT plans than for the ff-IMRT plans ( P = 0.012). In addition, the VMAT plans delivered fewer monitor units. The VMAT technique required a shorter planning time than the ff-IMRT technique (3.8 ± 0.8 hours vs. 5.4 ± 0.6 hours, P = 0.011). The major advantages of VMAT plans are higher efficiency and an approximately 50% reduction in delivery time compared with the ff-IMRT plans, with comparable plan quality. Further clinical investigations to evaluate the use of high-dose VMAT for the treatment of esophageal cancer are warranted.